Comparison of Zigbee, Z-Wave, Wi-Fi, and Bluetooth Wireless Technologies Used in Home Automation - Danbatta, Salim Jibrin; Varol, Asaf (Ieee, 2019)
Most of the home automation wireless technologies on the internet of things are based on ZigBee, Z-Wave, Wi-Fi, and Bluetooth wireless technologies. While these solutions are good enough, users of smart homes are facing challenges of selecting the best technology. This paper compares the performance of ZigBee, Z-Wave Wi-Fi and Bluetooth technologies from the user's perspective. Power consumption, range, cost, ease of use, scalability, and interoperability are the six indices developed as guidelines to potential users, and hence, the results of this study. With this knowledge, the users can make the appropriate choice of wireless technology solution to use in their home automation systems.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: internet of things; home automation; wireless technologies; Zigbee; Z-Wave; Wi-Fi; Bluetooth